1993
DOI: 10.1016/0735-1097(93)90600-6
|View full text |Cite
|
Sign up to set email alerts
|

Junctional tachycardia: A useful marker during radiofrequency ablation for atrioventricular node reentrant tachycardia

Abstract: We conclude that junctional tachycardia leading to AV block can be recognized by a faster junctional rate and ventriculoatrial block. This is a useful marker of impending AV block during slow and fast pathway ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(70 citation statements)
references
References 15 publications
2
66
2
Order By: Relevance
“…Although it was not referred to in the previous reports, the presence of Post-JR with a relatively short duration is recognizable in their figures. 3,4 Similarly we demonstrated that Post-JR remaining only for a few seconds (<10 s) was observed in 5% of the successful ablation sites (14% of the patients). Although actual data of the tissue temperature both during and after the RF application for ablation of AVNRT is lacking, the appearance of such short-term Post-JR could be attributed to the residual heating effect on the nodal or perinodal cells, because the Post-JR rate decelerated after termination of the RF delivery, leading to conversion to sinus rhythm, and was never resumed during the follow-up period.…”
Section: Electrophysiologic Mechanism Of the Post-jrmentioning
confidence: 82%
See 1 more Smart Citation
“…Although it was not referred to in the previous reports, the presence of Post-JR with a relatively short duration is recognizable in their figures. 3,4 Similarly we demonstrated that Post-JR remaining only for a few seconds (<10 s) was observed in 5% of the successful ablation sites (14% of the patients). Although actual data of the tissue temperature both during and after the RF application for ablation of AVNRT is lacking, the appearance of such short-term Post-JR could be attributed to the residual heating effect on the nodal or perinodal cells, because the Post-JR rate decelerated after termination of the RF delivery, leading to conversion to sinus rhythm, and was never resumed during the follow-up period.…”
Section: Electrophysiologic Mechanism Of the Post-jrmentioning
confidence: 82%
“…This phenomenon has also been postulated to be due to enhanced automaticity of AV nodal cells in response to thermal injury. 3,14 The underlying mechanism of junctional tachycardia was exclusively evaluated by Thibault et al using an in vitro animal model. 7 They demonstrated that heat-induced junctional tachycardia is most likely due to heat-induced acceleration of normal automaticity caused by an increase in the slope of phase 4 depolarization and shortening of the action potential duration.…”
Section: Electrophysiologic Mechanism Of the Post-jrmentioning
confidence: 99%
“…The incidence of this complication is considered low, with less than 1% in published studies 1,5,[16][17][18] . For that reason, in order to prevent complications such as TAVB during the ablation procedure, it is extremely important to observe the integrity of ventriculoatrial (V-A) conduction or the lengthening of the P-R interval 8,10,19,20 during JET. It is known that an A-V block, both transient and permanent, rarely occurs when V-A conduction remains intact during the entire period when JET occurs.…”
Section: Discussionmentioning
confidence: 99%
“…12,[15][16][17][18] The incidence of junctional beats during the successful ablation of AVNRT was 75-100%. The positive predictive value obtained in the present study is quite similar to those of prior reports.…”
Section: Junctional Beatsmentioning
confidence: 99%
“…Regardless of whether AVNRT was cured, junctional beats were induced when the slow pathway was injured by heat. 12,[15][16][17][18] In successful applications, the unit of slow pathway which responds to the temperature and induces junctional beats could be critical to maintain AVNRT, whereas in unsuccessful applications, there could be other units essential to AVNRT. The temperature required for the successful ablation of AVNRT differed markedly among the patients; one explanation is that the slow pathway may consist of multiple components present in various degrees in each patient.…”
Section: Main Findingsmentioning
confidence: 99%